CHARACTERISTICS OF MULTIPLE SCLEROSIS INCIDENCE IN THE NORTHERN REGIONS OF THE REPUBLIC OF AZERBAIJAN - Aliyev, R.R.; Mehtiyeva, Sh.N.; Shiraliyeva, R.K. (World of Medicine and Biology, 2025)
The purpose of this article was to study the incidence rate of Multiple Sclerosis (MS) in the northern areas of Azerbaijan, specifically the Sheki-Zagatala and Guba-Khachmaz economic regions, over the study period from January 1, 2013, to December 31, 2022. A total of 181 patients were confirmed with MS, with an average diagnostic age of 35.25±8.85 years and a female-to-male ratio of 1.62:1. The average age at the probable first MS attack was 29.57±8.59 years, with a diagnostic delay averaging 5.67±4.05 years. The most common type of MS was relapsing-remitting MS, observed in 82.87% of cases. Secondary-progressive MS was identified in 9.94% of patients. Over the 10-year study period, the average incidence of MS was 1.58±0.37 per 100,000 population, with rates of 1.96±0.57 per 100,000 in women and 1.20±0.45 per 100,000 in men. The average incidence in rural areas was 1.17±0.38 per 100,000, and in urban areas, it was 2.51±0.82 per 100,000.
Keywords: Azerbaijan; multiple sclerosis; epidemiology; incidence; population